EKSPRESI INDUCIBLE NOS YANG TINGGI SEBAGAI FAKTOR RISIKO NYERI NEUROPATI DIABETIK - Thomas Eko P* (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION PAINFUL DIABETIC NEUROPATHY PDN IS ONE OF THE MOST COMMON AND ANNOYING COMPLICATION OF DIABETES MELLITUS THE PATHOGENESIS OF PDN IS COMPLEX AND STILL UNCLEAR RECENLY IT HAS BECOME CLEAR THAT NITRIC OXIDE NO PLAY AN IMPORTANT ROLE IN PATHOGENESIS AND MAINTENANCE OF PERSISTENCY OF PAIN IN DNP